2009
DOI: 10.3340/jkns.2009.46.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Surgical Treatment for Symptomatic Adjacent Segment Degeneration after Lumbar Spine Fusion

Abstract: Objective : The present study analyzed the risk factors, prevalence and clinical results following revision surgery for adjacent segment degeneration (ASD) in patients who had undergone lumbar fusion. Methods : Over an 8-year period, we performed posterior lumbar fusion in 81 patients. Patients were followed a minimum of 2 years (mean 5.5 years). During that time, 9 patients required revision surgery due to ASD development. Four patients underwent autogenous posterolateral arthrodesis and extended transpedicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 22 publications
0
34
2
2
Order By: Relevance
“…Some authors believe that adjacent segment degeneration is related to age, sex, length of fusion segments, spinal sagittal alignment, and menopause [2,19,20]. Cho et al [21] found that elder patients was associated with higher incidence of adjacent segment degeneration after PLIF, therefore he thought that age was an important risk factor. Aota et al [22] found that the incidence of adjacent segment degeneration might increase significantly in patients older than 55 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that adjacent segment degeneration is related to age, sex, length of fusion segments, spinal sagittal alignment, and menopause [2,19,20]. Cho et al [21] found that elder patients was associated with higher incidence of adjacent segment degeneration after PLIF, therefore he thought that age was an important risk factor. Aota et al [22] found that the incidence of adjacent segment degeneration might increase significantly in patients older than 55 years.…”
Section: Discussionmentioning
confidence: 99%
“…The non-significant decrease in ODI score from 48.5±12.0 to 40.0±17.4 during final followup may suggest a worse natural history of spine pathology in ASD patients. It is possible that patients requiring surgery for ASD may be biased towards a natural history that is (19). Direct comparison of surgical techniques for treatment of ASD should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…[3,6,8,9,12,16,17] Although recent biomechanical studies have shown that a number of spinal devices can be used for rigid fixation and fusion at the treated level, little attention has been focused on the adjacent segment instability. [2,5,6,8,12,13,[16][17][18] The present study focused on the adjacent segment instability. As adjacent segment mobility increased, the anterior and posterior structures maintained stability and prevented instability.…”
Section: Discussionmentioning
confidence: 99%
“…The second theory posits that degeneration of the adjacent segment is indicative of the natural degenerative course of an aging disc. [3,[7][8][9]13,14] In this study, we aimed to investigate the mechanical behavior and instability of the adjacent segment following rigid fixation.…”
Section: Methodsmentioning
confidence: 99%